Superheroes, women, and visual pleasure: The construction of the female gaze in the marvel cinematic universe - Szujer, Orsolya (AMERICANA E-journal of American Studies in Hungary, 2018)
The paper analyses how the female gaze is present in selected movies in the Marvel Cinematic Universe, primarily based on Laura Mulvey’s theory on the male gaze and Richard Dyer’s observations on the instability of the male pinup. Before delving into the study of how the eroticized male (super)body is presented in the MCU, I briefly outline the current situation of women in the superhero fandom, with emphasis on the growth of female audience in the case of comic book blockbuster movies and how the presence of an eroticized male body might be a tool for gaining female audience. I will analyze Captain America: The First Avenger (2011), the Thor–trilogy—Thor (2011), Thor: The Dark World (2013), and Thor: Ragnarok (2017) and Black Panther (2018).